Model for home-preschool continuity in linguistically and culturally diverse settings - Mila Schwartz; Hanna Ragnarsdóttir (Frontiers in Psychology)
With the advent of international freedom of movement, we are witnessing a rapid influx of children from diverse linguistic and cultural backgrounds in mainstream preschools. Preschool education scholars have argued that teachers must work collaboratively with these children’s families to support their “linguistic security” and well-being. The paper presents a conceptual model integrating linguistically and culturally responsive teaching with family funds of knowledge, language education, and family language policies. It highlights the interaction between these constructs that may lead to home-preschool continuity. The model is firmly grounded in three theoretical perspectives: Bronfenbrenner’s ecological model, which emphasizes the importance of the environment in a child’s development; Epstein’s model of parental involvement, which highlights the various ways parents can be involved in their child’s education; and Schwartz’s concept of agency in interactions between teachers and parents, which underscores the importance of mutual understanding and collaboration between these two agents. The model has the potential to guide research focusing on parents’ and teachers’ agency in enacting language policy and addressing cultural values. With its transformative potential, this model opens horizons for practical solutions for the interaction between these agents.